Aerodynamic study on go-kart using computer aided tools / Mohd Yusri Abu Bakar - Abu Bakar, Mohd Yusri (2005)
In recent years, go-kart bodywork design has been improved in terms of its aerodynamic characteristic. The author had conducted an analysis using computer aided tools beginning from creation of a 3D model of an existing go-kart design to CFD simulation to determine the aerodynamics characteristic of the go-kart. Optimization process of the go-kart bodywork design based on the results of existing go-kart simulation was conducted. Using the result obtained a new optimized go-kart bodywork parameters were established. An analysis to determine the optimization parameters between the existing and the optimized bodywork was performed. The results of the analysis was discussed and concluded accordingly. Few problems encountered, mostly in the development of the analysis domain and the mesh for the domain. Remedies and suggestions for future study were discussed as a reference in the future.